Determination of Nineteen Kinds of Mineral Elements Content of Genetically Modified Antidwarf Mosaic Maize by AES, AAS and ICP-MS - Yan, Pingmei; Wang, Qing; Yan, Xiaoyan; Chang, Xiao-Hui; Du, Jian-zhong; Sun, Yi (Asian Journal of Chemistry, 2012)
Genetically modified food safety has become a hot issue of food safety assessment since its birth. Genetically modified antidwarf mosaic maize were selected to research the change of mineral elements as a part of genetically modified food safety. The results showed that concentrations of thirteen kinds of mineral elements descend in genetically modified antidwarf mosaic maize compared with its parent, they are K, Mg, Zn, P, Fe, V, Mn, Cu, As, Se, Li, Mo and Cd, especially Zn and Fe reached the significant level; the increasing elements are Na, Ca, Cr, Pb, Co and Ni, in which Na, Ca, Cr and Pb reached the significant level. So genetically modified food safety evaluation should not to be taken lightly, we should always be on the strict control of genetically modified foods as before.